Question: Consider the following proposed rule for functional dependencies
Consider the following proposed rule for functional dependencies: If α → β and γ → β, then α → γ. Prove that this rule is not sound by showing a relation r that satisfies α → β and γ → β, but does not satisfy α → γ.
Answer to relevant QuestionsUse Armstrong’s axioms to prove the soundness of the union ruleUsing the functional dependencies of Exercise 7.11, compute the canonical cover Fc.List the three design goals for relational databases, and explain why each is desirable.Give an example of a relation schema R and a set of dependencies such that R is in BCNF, but is not in 4NF.Why do persistent programming languages allow transient objects? Might it be simpler to use only persistent objects, with unneeded objects deleted at the end of an execution? Explain your answer.
Post your question